2002
DOI: 10.1007/s00425-002-0829-y
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of plasma-membrane NADPH oxidase in abscisic acid- and water stress-induced antioxidant defense in leaves of maize seedlings

Abstract: The roles of the plasma-membrane (PM) NADPH oxidase in abscisic acid (ABA)- and water stress-induced antioxidant defense were investigated in leaves of maize ( Zea mays L.) seedlings. Treatment by exogenous ABA (100 micro M ABA) or osmotic stress (-0.7 MPa induced by polyethylene glycol) significantly increased the activity of the PM NADPH oxidase, the production of leaf O(2)(-), the activities of several antioxidant enzymes (superoxide dismutase, catalase, ascorbate peroxidase and glutathione reductase), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
223
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 339 publications
(234 citation statements)
references
References 62 publications
9
223
1
1
Order By: Relevance
“…NOX acts as a supplier of ROS which is needed for signal transduction and stress perception in plants [64]. Many studies have shown that NOX activity increases under drought stress [34,65]. In agreement with these studies, we also observed a strong increase in NOX activity in both Cleome species.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…NOX acts as a supplier of ROS which is needed for signal transduction and stress perception in plants [64]. Many studies have shown that NOX activity increases under drought stress [34,65]. In agreement with these studies, we also observed a strong increase in NOX activity in both Cleome species.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the level of lipid peroxidation was determined by measuring MDA content, which is a product of lipid peroxidation. Maintenance of membrane functionality due to unchanged MDA content in C. gynandra under drought stress may be attributed to the adequate response of the antioxidant system to drought-induced oxidative damage, as also observed in some other stress-tolerant plants such as maize [34], sorghum [5] and Plantago maritima [67]. On the other hand, in C. spinosa, increased MDA depending on time of drought treatment showed that the effect of antioxidant defence was insufficient under stress conditions to suppress the increasing ROS production.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, ROS may also serve as a molecules transducting drought signal and so enhance the plant stress defense mechanisms (Guan and Scandalios, 1998;Guan et al, 2000;Yoshimura et al, 2000;Jiang and Zhang et al, 2002;Noctor, 2005;Suzuki and Mittler, 2006). There are basically two detoxification mechanisms plants have developed to scavenge free ROS (Scandalios, 1997;Shalata and Tal, 1998;Procházková et al, 2001) (i) Non-enzymatic radical scavengers, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence indicates that ABAenhanced water stress tolerance is, at least in part, due to the induction of antioxidant defense systems [3][4][5][6]. Previous studies have shown that NADPH oxidase, hydrogen peroxide (H 2 O 2 ), nitric oxide (NO), calcium (Ca 2+ )-calmodulin (CaM), and mitogen-activated protein kinase (MAPK) are required for ABA-induced up-regulation in the activities of antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX) and glutathione reductase (GR) in leaves of maize plants [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%